Pengembangan E-Modul Berbasis Pendekatan Contextual Teaching and Learning (CTL) pada Materi SPLDV - Rosmery, Linda (Jurnal Pendidik Indonesia, 2025)
This study employed a Research and Development (R&D) approach aimed at developing an e-module based on the Contextual Teaching and Learning (CTL) approach for the topic of Systems of Linear Equations in Two Variables (SLETV) for eighth-grade junior high school students. The development process followed the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The trial participants involved 38 students and one mathematics teacher at SMP Negeri 5 Tanjungpinang. Data were collected using expert validation questionnaires and user practicality questionnaires. The validation results indicated that the e-module achieved a validity level of 88.00% from the subject-matter expert, categorized as valid, and 90.00% from the media expert, categorized as very valid. Furthermore, the practicality test showed that the teacher and student responses reached 89.33% and 90.91%, respectively, both classified as very practical. Based on these findings, the developed CTL-based e-module is considered valid and practical for supporting the teaching and learning of systems of linear equations in two variables at the junior high school level.